2013
DOI: 10.1098/rsif.2012.1065
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopic analyses of unique yellow feather pigments (spheniscins) in penguins

Abstract: Many animals extract, synthesize and refine chemicals for colour display, where a range of compounds and structures can produce a diverse colour palette. Feather colours, for example, span the visible spectrum and mostly result from pigments in five chemical classes (carotenoids, melanins, porphyrins, psittacofulvins and metal oxides). However, the pigment that generates the yellow colour of penguin feathers appears to represent a sixth, poorly characterized class of feather pigments. This pigment class, here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 77 publications
2
65
1
Order By: Relevance
“…Additionally, results in Thomas et al. (2013) conflict with the ones reported by Galván et al. (2013b), who characterized the Raman spectrum of pheomelanin, again not including fluorescence but wide Raman bands at about 500, 1490, and 2000 cm −1 (Galván et al.…”
Section: Introductioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Additionally, results in Thomas et al. (2013) conflict with the ones reported by Galván et al. (2013b), who characterized the Raman spectrum of pheomelanin, again not including fluorescence but wide Raman bands at about 500, 1490, and 2000 cm −1 (Galván et al.…”
Section: Introductioncontrasting
confidence: 74%
“…They therefore concluded that this fluorescence response is diagnostic for melanins (Thomas et al. 2013). In another study, feathers excited with a 1064-nm laser resulted in a Raman band around 1100 nm that was assigned to melanin (Thomas et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Raman spectroscopy provides a non-destructive, fast and easy way to identify pigments in situ with almost no sample preparation. With Raman spectroscopy, pigmentary colours can be readily categorized into one of the few more common groups of pigments by comparing their Raman signature signals to expedite further biochemical analyses using HPLC and/or MS. Raman spectroscopy has identified many different types of pigments in bird feathers (Galván et al, 2013;Thomas and James, 2016;Thomas et al, 2013) but has rarely been applied to spiders. Thus, we developed a workflow that begins with Raman spectroscopy to evaluate long-standing assumptions about pigmentary colours in spiders.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms for accumulating at least 6 chemically distinct groups of pigments in feathers have evolved within birds or their nonavian ancestors (McGraw 2006b, Thomas et al 2013. Carotenoid plumage pigments (red, orange, yellow, pink, purple) are honest signals of fitness for some species (Hill 1990) and apparently have multiple, ancient origins (Thomas et al 2014a).…”
Section: Introductionmentioning
confidence: 99%